Influence of anion substitution on electrical conductivity of composites based on liquid crystal with Cu₆PS₅X (X = I, Br) nanoparticles - Studenyak, I.P.; Kovalchuk, O.V.; Poberezhets, S.I.; Timko, M.; Kopcansky, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Dielectric properties of composites based on planar-oriented 6СВ liquid crystal with Cu₆PS₅X (X = I, Br) nanoparticles at 293 K in the frequency range from 6 to 10⁶ Hz have been studied. The concentration of nanoparticles varied from 0 to 0.1 wt.%. It has been shown that Cu₆PS₅Вr nanoparticles significantly less influence the conductivity of 6CB than the Cu₆PS₅I nanoparticles. Moreover, at the concentrations 0.01 to 0.05 wt.% of Cu₆PS₅Br nanoparticles, the conductivity of the LC decreases. It has been assumed that the nonmonotonic dependence of 6CB conductivity on the concentration of Cu₆PS₅Br superionic nanoparticles is caused by two competing mechanisms: an increase in conductivity due to the introduction of conductive impurities with nanoparticles and a decrease in conductivity caused by adsorption of impurities on the surface of nanoparticles.